Defects on activated carbon determine the dispersion of active components and thus the simultaneous removal efficiency of SO2, NOx and Hg0. (1st June 2021) - Qin, Yuan; Wang, Chi; Sun, Xin; Ma, Yixing; Song, Xin; Wang, Fei; Li, Kai; Ning, Ping
Graphical abstract: Highlights: Carbonization temperature affects surface defects and 700 °C is optimal. Surface defects affects the dispersion of active components. Highly dispersed Fe/WSC catalyst performed high simultaneous removal efficiency. The stronger interaction between Fe and gas molecules promoted the activity. Abstract: The smelting industry (such as lead–zinc smelting) is an important part of China's industrial production, and a large amount of SO2, NOx, and heavy metal (mercury, arsenic, etc.) are inevitable in the exhaust gas. The harm of these components to human health and the environment has long been established, so the simultaneous removal of SO2, NOx and Hg 0 is urgent and meaningful. In this paper, walnut shell based carbon (WSC) was prepared by using solid waste walnut shell as the original material firstly, and then the simultaneous removal catalysts were prepared by modifying WSC with transition metals. In this process, we focused on the effect of carbonization temperature on the surface and structural properties of the catalyst. Research has found that the carbonization temperature will affect the pore structure and surface defects of activated carbon, thereby affecting the dispersion of active components, which in turn affects the activity of the catalysts for the simultaneous removal of SO2, NOx and Hg 0 . Activity evaluation combined with DFT theoretical calculation results show that Fe dominates among a variety of transition metals, and Fe/WSC catalyst can achieve a simultaneous removal efficiency of more than 80% in the temperature range of 300–350°.